Liver-innervating vagal sensory neurons are indispensable for the development of hepatic steatosis and anxiety-like behavior in diet-induced obese mice - Jiyeon Hwang; Sangbhin Lee; Junichi Okada; Li Liu; Jeffrey E. Pessin; Streamson C. Chua; Gary J. Schwartz; Young-Hwan Jo (Nature Communications)
Abstract The visceral organ-brain axis, mediated by vagal sensory neurons, is essential for maintaining various physiological functions. Here, we investigate the impact of liver-projecting vagal sensory neurons on energy balance, hepatic steatosis, and anxiety-like behavior in mice under obesogenic conditions. A small subset of vagal sensory neurons innervate the liver and project centrally to the nucleus of the tractus solitarius, area postrema, and dorsal motor nucleus of the vagus, and peripherally to the periportal areas in the liver. The loss of these neurons prevents diet-induced obesity, and these outcomes are associated with increased energy expenditure. Although males and females exhibit improved glucose homeostasis following disruption of liver-projecting vagal sensory neurons, only male mice display increased insulin sensitivity. Furthermore, the loss of liver-projecting vagal sensory neurons limits the progression of hepatic steatosis. Intriguingly, mice lacking liver-innervating vagal sensory neurons also exhibit less anxiety-like behavior compared to control mice. Modulation of the liver-brain axis may aid in designing effective treatments for both psychiatric and metabolic disorders associated with obesity and MAFLD.